GROUNDWATER VULNERABILITY TO POLLUTION IN KASIHAN DISTRICT, BANTUL REGENCY, INDONESIA - Purnama, Setyawan; Cahyadi, Ahmad (Forum Geografi, 2019)
The groundwater vulnerability to pollution refers to the ease of pollutants reaching groundwater, so the groundwater will be polluted. The concept shows a probability that pollution will occured which basically bases on the assumption that the physical environment can prevent the flow of pollutants into the aquifer. The purpose of this study was to predict the vulnerability of groundwater in the study area against pollution. To achieve these objectives beside base on secondary data, also measured the depth of phreatic surface, slope and groundwater sampling. Location of measurement and sampling is determinated by considering location of infiltration measurement ever done by Purnama in 2017. To conduct groundwater vulnerability analysis on pollution in the study area, carried out by SINTACS Method which bases on a numerical system of weight and rating. Weight are determined based on the significance of the effect of the parameters on groundwater pollution, while the rating is determined based on the significance of the influence of variables in each parameters against groundwater pollution. As a result, it is known that groundwater vulnerability indeks in research area range from 117,0 to 189,9. According to criteria of SINTACS, the value are classified as moderate vulnerability and rather high vulnerability. Areas that include moderate levels of vulnerability generally located in Sentolo Formations that consist of limestone and has grumusol soil type. Areas that classified as rather high vulnerability is located in Yogyakarta Formation that consist of volcanic rock and has regosol soil type. Based on this phenomena, it can be said that geological aspect and type of soil greatly affect the vulnerability of groundwater to pollution in the research area.